Philosophical Perspectives on Galen of Pergamum: Four Case-Studies on Human Nature and the Relation between Body and Soul - Vinkesteijn, Robert (Brill, 2022)
This is a ground-breaking philosophical-historical study of the work of Galen of Pergamum. It contains four case-studies on (1) Galen's remarkable and original thoughts on the relation between body and soul, (2) his notion of human nature, (3) his engagement with Plato's Timaeus, (4) and black bile and melancholy. It shows that Galen develops an innovative view of human nature that problematizes the distinction between body and soul.